Determination of natural radioactivity levels in drinking water and soil at APA Passaúna (Curitiba, PR) - Rodrigo Sanas Zamboni; Camila Sampaio Nogueira; Sergei Paschuk; Janine Correa (Brazilian Journal of Radiation Sciences)
Natural radioactive materials have been part of the ecosystem since the formation of the Earth. Monitoring these nuclides in rocks, soils, groundwater, and air is essential for the scientific community and for implementing mitigation measures. This is because radon decay products are the second leading global cause of lung cancer, after tobacco. This study focused on conducting a radiometric survey of properties in the APA Passaúna, Curitiba (PR). The AlphaGUARD PQ2000 PRO equipment was used to measure the concentrations of 222Rn and 226Ra in well water and 222Rn and 220Rn in soil air. Gamma spectrometry was conducted with the portable scintillator BRD-AT6101C. The analysis revealed the presence of 40K in all the investigated sites, as expected, along with lower amounts of 226Ra and 232Th. Radiation dose equivalents were generally low, except at a specific point where the estimated dose was 1.65 μSv/h, with a 220Rn concentration of (664 ± 36) kBq/m³. Seven out of the nine wells studied showed a committed effective dose value for the ingestion and inhalation of drinking water above the reference level set by the WHO (0.1 mSv/year). The excess values ranged from 0.106 to 0.385 mSv/year. In contrast, radon concentrations in indoor air ranged from (30 ± 2) to (270 ± 20) Bq/m³, within normal parameters. According to the CNEN standard NN 3.01, the study complies with Brazilian radioprotection standards and has significant social relevance, especially in a region where water is predominantly sourced from wells. These data are preliminary for the southern region of Brazil and highlight the need for further scientific research.